Gibberellin biosynthesis: enzymes, genes and their regulation - Hedden, P. (University of Bristol, UK.); Kamiya, Y (Annual review of plant physiology and plant molecular biology, 1997)
▪ Abstract  The recent impressive progress in research on gibberellin (GA) biosynthesis has resulted primarily from cloning of genes encoding biosynthetic enzymes and studies with GA-deficient and GA-insensitive mutants. Highlights include the cloning of ent-copalyl diphosphate synthase and ent-kaurene synthase (formally ent-kaurene synthases A and B) and the demonstration that the former is targeted to the plastid; the finding that the Dwarf-3 gene of maize encodes a cytochrome P450, although of unknown function; and the cloning of GA 20-oxidase and 3β-hydroxylase genes. The availability of cDNA and genomic clones for these enzymes is enabling the mechanisms by which GA concentrations are regulated by environmental and endogenous factors to be studied at the molecular level. For example, it has been shown that transcript levels for GA 20-oxidase and 3β-hydroxylase are subject to feedback regulation by GA action and, in the case of the GA 20-oxidase, are regulated by light. Also discussed is other new information, particularly from mutants, that has added to our understanding of the biosynthetic pathway, the enzymes, and their regulation and tissue localization.